2018
DOI: 10.1038/s41598-018-29616-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K supplementation during pregnancy for improving outcomes: a systematic review and meta-analysis

Abstract: To study supplementation effect of vitamin K (VK) alone or combined with other nutrients administered to pregnant women, we searched Cochrane Pregnancy and Childbirth Group’s Trials Register (till 22 January 2016, updated on 28 February 2018) including other resources. Two review authors independently assessed randomised or quasi-randomised controlled trials for inclusion, data extraction, accuracy, and risk of bias. We included older trials from high-income countries (six; 21,493 women-newborns), judged mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…However, a systematic review of the literature on antiepileptic drug use in pregnancy revealed that there was insufficient evidence to support vitamin K supplementation in the last weeks of pregnancy to reduce the risk of VKDB [55]. Further studies are required to establish a prophylactic strategy to prevent early-onset VKDB [56].…”
Section: Prevention Of Vkdb In Infancy and Prophylaxis Guidelinesmentioning
confidence: 99%
“…However, a systematic review of the literature on antiepileptic drug use in pregnancy revealed that there was insufficient evidence to support vitamin K supplementation in the last weeks of pregnancy to reduce the risk of VKDB [55]. Further studies are required to establish a prophylactic strategy to prevent early-onset VKDB [56].…”
Section: Prevention Of Vkdb In Infancy and Prophylaxis Guidelinesmentioning
confidence: 99%
“…This observation could be newborn piglets ingested enough vitamin K from their milk and creep feed, while their bodies stored rich menadione. Shahrook et al employed a meta-analysis to investigate the outcomes of vitamin K supplementation on pregnancy [43]. The author found that the antenatal vitamin K increased neonatal plasma vitamin K and breast milk vitamin K [43].…”
Section: Influence Of Vitamin Form and Vitamin Level On Plasma Vitamimentioning
confidence: 99%
“…Shahrook et al employed a meta-analysis to investigate the outcomes of vitamin K supplementation on pregnancy [43]. The author found that the antenatal vitamin K increased neonatal plasma vitamin K and breast milk vitamin K [43]. The concentration of plasma vitamin K 3 increases when the dietary level of vitamins increases, which suggests that an improved vitamin K status may enhance alternative metabolic pathways through mechanisms beyond vitamin K's classic role as an enzyme cofactor.…”
Section: Influence Of Vitamin Form and Vitamin Level On Plasma Vitamimentioning
confidence: 99%
“…This, in turn, could lead to spontaneous abortion and embryopathy during the first trimester and CNS abnormalities, fatal hemorrhage and stillbirth at any stage during pregnancy (13)(14)(15)(16). In addition, safety of prolonged, off-label administration of daily pharmacologic doses (~100 mg) of oral VK 1 in pregnant women and their fetuses has not been established (17)(18)(19). For instance, fetal health may be susceptible to redox-modulating effects of menadione, an endogenous metabolite of oral VK 1 , that elaborates tissuedamaging reactive oxygen species (20,21).…”
Section: Discussionmentioning
confidence: 99%